1990
DOI: 10.1116/1.576485
|View full text |Cite
|
Sign up to set email alerts
|

Ion energetics in electron cyclotron resonance discharges

Abstract: Measurements have been made of ion energies in an electron cyclotron resonance plasma, under conditions typically employed for semiconductor materials processing. Both ion energies along magnetic field lines and ion energy distributions generated by a radio frequency (rf) sheath are characterized. Ion impact energies are found to vary between 10 and 35 eV under the conditions studied, with corresponding distribution widths from 3 to 8 eV. Ion energy distributions through an rf sheath are found to be highly dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In typical manufacturing plasma processes, ion energy is coarsely controlled by varying the amplitude of a rf sinusoidal bias voltage applied to the substrate electrode, but the resulting ion energy distribution function ͑IEDF͒ is generally broad. 1,2 The energy provided to the substrate surface upon ion impact can enhance chemical reactions via several mechanisms, demonstrated in simulation and ion beam experiments, with significant implications for etched feature profiles and etch selectivity, 3,4 as well as film quality in plasma enhanced physical vapor deposition ͑PECVD͒ processes. 5 Control of the width of the IEDF at the substrate has the potential for significantly improving these aspects of plasma processes, and for improving understanding of the role ions play.…”
Section: Introductionmentioning
confidence: 99%
“…In typical manufacturing plasma processes, ion energy is coarsely controlled by varying the amplitude of a rf sinusoidal bias voltage applied to the substrate electrode, but the resulting ion energy distribution function ͑IEDF͒ is generally broad. 1,2 The energy provided to the substrate surface upon ion impact can enhance chemical reactions via several mechanisms, demonstrated in simulation and ion beam experiments, with significant implications for etched feature profiles and etch selectivity, 3,4 as well as film quality in plasma enhanced physical vapor deposition ͑PECVD͒ processes. 5 Control of the width of the IEDF at the substrate has the potential for significantly improving these aspects of plasma processes, and for improving understanding of the role ions play.…”
Section: Introductionmentioning
confidence: 99%
“…These trends are consistent with Uhm's theoretical report 12 and experimental measurement. [5][6][7][8] When an ion injects into the substrate, its impact angle is generally not perpendicular to the surface. Defining the ion impact radial pitch angle as arctg( r / z ), the ion impact radial angle distributions for various pressures are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, ion energy, velocity distribution functions and temperature have been investigated in detail experimentally. [3][4][5][6][7][8][9][10][11] For example, Sadghi et al 3 reported a detailed measurement of ion velocity distributions in both the source and reactor region in an ECR system. King and co-workers 5 have investigated the ion energy distribution in two magnetic field configurations.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the electrons are represented by a Boltzmann distribution n,(x)=ndexp e@(x) ( 1 kTe , (3) where a(x) is the electrostatic potential, n,, is the electron density at x=0, where Q> is defined to be zero, and k is the Boltzmann constant.…”
Section: Simulation Model and Assumptionsmentioning
confidence: 99%